The Effect of Work Life Balance and Work Environment on Job Satisfaction with Motivation as an Intervening Variable at PT PLN Indonesia Power UBP Barru - La Ode Muhammad Asrul; Kabul Wahyu Utomo; Sahnaz Ubud (Eduvest - Journal of Universal Studies, 2025)
Job satisfaction is crucial in human resource management as it directly impacts employee performance, loyalty, and productivity. This study examines the influence of work-life balance and work environment on job satisfaction, with motivation as an intervening variable, among employees of PT PLN Indonesia Power UBP Barru. The study is motivated by fluctuations in job satisfaction data and the demanding nature of the electrical energy sector, which includes high workloads, shift work, and safety risks. Using a quantitative approach and the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique, data were collected through questionnaires distributed to respondents selected by stratified random sampling, while secondary data were obtained from company reports and literature. The research variables included work-life balance (X1), work environment (X2), motivation (Z), and job satisfaction (Y). The results show that both work-life balance and work environment significantly impact job satisfaction, and that they positively influence motivation. Furthermore, motivation significantly affects job satisfaction and mediates the relationship between work-life balance, work environment, and job satisfaction. These findings align with Herzberg's Two-Factor Theory, which suggests that both motivator and hygiene factors contribute to job satisfaction. Therefore, this study highlights the importance of improving work-life balance, work environment, and motivation to enhance employee job satisfaction in the energy sector.